Comparative macroanatomical investigations on (he veins superficial and profund of ihe head in akkaraman sheep and angora goat - Hakan Yalçın; Sadettin Tıpırdamaz (Eurasian Journal of Veterinary Sciences)
Eight Akkaraman sheep and eight Angora goat provided Konya environment were used in this study. Investigation ol these materials was used Latex, Mettıymethacrylate and Baryum Sultat. It was observed that in the course of the external jugular vein in jugular groove receives the superficial cervical vein, cephalic vein, medial thyroid vein, cranial thyroid vein, occipital vein, linguofacial vein and maxillary vein. It was observed that linguofacial veins was formed by joining lingual and maxillary veins at the caudal level of mandibular angle, tt was determined that the pterygoid plexus formed by the palatinal veins, masseteric vein, buccal vein and pterygoideal veins while pharyngeal veins, inferior alvolar vein and profund temporal vein directly joined maxillary vein.